6 The consequences of knee joint injury in youth sport. (19th April 2018) - Whittaker, Jackie; Toomey, Clodagh; Jaremko, Jacob; Emery, Carolyn
Abstract : Introduction: Youth sport participants are vulnerable to joint injury and subsequent osteoarthritis. Improved understanding of the period following joint injury could inform osteoarthritis prevention strategies. This research examines the association between youth sport-related knee injury and health-related outcomes, 3–10 years post-injury. Methods: Participants include 100 youth who experienced a sport-related knee injury 3–10 years previously and 100 age, sex and sport-matched uninjured controls. Outcomes include: Knee Injury and Osteoarthritis Outcome Score (KOOS); Intermittent and Constant Osteoarthritis Pain; body mass index (BMI), fat mass index (FMI); weekly physical activity; estimated VO2 max; hip and knee muscle strength; dynamic balance; MRI and radiographic-defined osteoarthritis. After describing baseline characteristics multivariable conditional regression (95% CI) was used to evaluate the association between injury history and each outcome, considering differences by sex, time-since-injury and injury type. Results: Participant median age was 22 years (range 15–26) and 55% were female. The previously injured group reported poorer KOOS scores, more intermittent pain, higher BMI (1.8 kg/m 2 ; 95% CI: 0.9 to 2.6) and FMI (1.1 kg/m 2 ; 0.5, 1.6), weaker knee muscles (−0.21 Nm/kg; −0.0031, –0.011), poorer balance and more frequent MRI-defined OA (OR 10.0; 2.3, 42.8) than controls. Greater differences in KOOS, BMI, FMI, VO2 max, knee muscle strength, and balance existed between injured and uninjured females than males. Longer time-since-injury influenced the association between previous injury and KOOS, knee extensor strength and balance. Conclusions and relevance: Outcomes consistent with future osteoarthritis and other negative health states are more prevalent in individuals 3–10 years following a range of youth sport-related knee injuries compared to uninjured matched controls.